Communicating through music: a tool for students' inspirational development (Journal of Applied Learning and Teaching, 2021)
Showing and discussing examples of how people achieve goals can become a great source of inspiration (Piirto, 2011). Young people, especially students of different socio-cultural backgrounds, should be initiated and engaged in authentic projects and ideas. This article gives concrete reasons to K-12 and higher education stakeholders of why and how such projects should become part of curricula. This case study presents the creation of a multicultural disc in three languages (Greek, Corsican, and French) as an attempt to add to the inspirational development of students to aid teachers to achieve overall educational aims.